A new species, new synonymy and new records of Mexican and Central American Xyleborini (Coleoptera: Curculionidae: Scolytinae) - Atkinson, Thomas H. (Zootaxa, 2018)
Coptoborus silviasalasi Atkinson, new species is described from Oaxaca, Mexico. New synonyms include: Dryocoetoides capucinus Eichhoff, 1869 (=monachus Blandford, 1898) and Taurodemus sharpi Blandford, 1898 (= sharpi lenis Wood, 1974). Significant new distribution records are given for Xyleborini from Mexico and Central America.